БУЮК ТАСВИРИЙ САНЪАТ УСТАЛАРИ ИЖОДИНИНГ УЗЛУКСИЗ ТАЪЛИМДАГИ ЎРНИ (Scientific journal of the Fergana State University, 2023)
This article is about initially academic drawing and the composition of  famous painter’s creative works as well as the importance of step by step  in uninterrupted  education.